Two new genera of Punctulina and description of a new species of Clavoreticula (Hemiptera: Cicadellidae: Deltocephalinae: Vartini) from Mainland Southeast Asia - Lin, You-Sheng; Dietrich, Christopher H.; Shiao, Shiuh-Feng (Zootaxa, 2026)
The present study describes five new taxa of the deltocephaline subtribe Punctulina from Mainland Southeast Asia, including a new species of Clavoreticula (C. gracilis sp. nov. from Thailand) and two new genera (Paraclavoreticula gen. nov. with its type species P. triangularis sp. nov. from Thailand and Sembokia gen. nov. with its type species S. gotzeki sp. nov. from Cambodia). The diagnostic characters for these new taxa are illustrated. Updated keys to species of Clavoreticula and genera of Punctulina are provided.